Overwintering Survival of Drosophila suzukii (Diptera: Drosophilidae) and the Effect of Food on Adult Survival in California's San Joaquin Valley. Issue 4 (11th December 2015) - Kaçar, Gülay; Wang, Xin-geng; Stewart, Thomas J.; Daane, Kent M.
Abstract : The overwintering survival and development of Drosophila suzukii Matsumura were investigated in California's San Joaquin Valley. Drosophila suzukii were exposed to overwintering conditions in cages hung in a citrus orchard, and the pupae were buried in the soil. Eggs exposed from late November to January did not survive; a low percentage (<3%) of larvae and pupae developed into adults. Survival of pupae was significantly higher when buried in the soil than on the citrus tree. From late January to March, all life stages developed into adults and overwintered adult female D. suzukii produced eggs when provided with 10% honey-water and sliced oranges. Adult survival varied among fruit juice provision treatments and overwintering exposure periods, ranging from 3.4 ± 0.9 d (water) to 44.1 ± 3.0 d (10% honey-water). Fruit juices of apple, cherry, grape, orange, and pomegranate were tested as adult food sources; results showed that adult female and male D. suzukii lived only 2 d with water only, whereas adults survived from 14.2 to 34.8 d with fruit juice treatments and the 10% honey-water control. An unexpected event was the oviposition and immature development of D. suzukii with the fruit juice. In a follow-up laboratory trial, when 10% honey-water or orange juice were provided along with an artificial diet for oviposition and immature development, female D. suzukii survived for 21.6 ± 2.4 or 21.6 ± 1.5 d, and produced 106.8 ± 14.1 or 98.5 ± 13.1 offspring, respectively. We discuss factors potentially influencing overwintering survival of D. suzukii.